Causes of medication errors in intensive care units from the perspective of healthcare professionals - Sedigheh Farzi; Alireza Irajpour; Mahmoud Saghaei; Hamid Ravaghi (Wolters Kluwer Medknow Publications, 2017)
Objective: This study was conducted to explore and to describe the causes of medication errors in Intensive Care Units (ICUs) from the perspective of physicians, nurses, and clinical pharmacists. Methods: The study was conducted using a descriptive qualitative method in 2016. We included 16 ICUs of seven educational hospitals affiliated to Isfahan University of Medical Sciences. Participants included 19 members of the healthcare team (physician, nurse, and clinical pharmacist) with at least 1 year of work experience in the ICUs. Participants were selected using purposeful sampling method. Data were collected through semi-structured individual interviews and were used for qualitative content analysis. Findings: The four main categories and ten subcategories were extracted from interviews. The four categories were as follows: "low attention of healthcare professionals to medication safety," "lack of professional communication and collaboration," "environmental determinants," and "management determinants." Conclusion: Incorrect prescribing of physicians, unsafe drug administration of nurses, the lack of pharmaceutical knowledge of the healthcare team, and the weak professional collaboration lead to medication errors. To improve patient safety in the ICUs, healthcare center managers need to promote interprofessional collaboration and participation of clinical pharmacists in the ICUs. Furthermore, interprofessional programs to prevent and reduce medication errors should be developed and implemented.